Dual-step hybrid SERS scheme through the blending of CV and MoS2 NPs on the AuPt core-shell hybrid NPs. (30th April 2022) - Mandavkar, Rutuja; Lin, Shusen; Kulkarni, Rakesh; Pandit, Sanchaya; Burse, Shalmali; Habib, Md Ahasan; Pandey, Puran; Kunwar, Sundar; Lee, Jihoon
Highlights: Demonstration of AuPt hybrid core-shell and fully alloyed bi-metallic NPs by the two-step solid-state dewetting. Demonstration of dual-step hybrid SERS with MoS2 NPs and AuPt hybrid core-shell NPs. Demonstration of significantly enhanced SERS of crystal violet. Demonstration of FDTD simulations for various hybrid configurations: i.e., HNPs, alloy NPs, MoS2 /HNPs. Abstract: Along with a wide range of applications, the surface-enhanced Raman spectroscopy (SERS) is a prominent analytical technique to recognize and detect molecules and materials even at an extremely low molar concentration. In this work, a unique hybrid SERS platform is demonstrated by the incorporation of molybdenum disulfate (MoS2 ) nanoparticles (NPs) onto the core-shell AuPt hybrid NPs (HNPs) for the enhanced molecular Raman vibration of crystal violet (CV). The hybrid platform takes the advantage of both the electromagnetic mechanism (EM) offered by the AuPt HNPs and chemical mechanism (CM) owing to the MoS2 NPs. The distinctive core-shell morphology of AuPt HNPs with the high-density background Au NPs is attained by a unique two-step solid-state dewetting method, which can offer a high concentration of electromagnetic hot spots. At the same time, the MoS2 NPs can provide an ample charge transfer with abundant active sites. Through the hybrid SERS approach, a dramatic SERS enhancement of CV Raman vibration is demonstrated, and the SERS capability is thoroughly studied. In addition, the finite-difference time-domain (FDTD) simulations provide a deeper understanding of the electromagnetic field distributions for various configurations of nanostructures and their hybrid combinations: i.e., HNPs, alloy NPs, MoS2 /HNPs configurations. Graphical abstract: Image, graphical abstract